2003
DOI: 10.1007/s10162-002-2058-2
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analyses of Mouse Inner-Ear Transcripts

Abstract: The development and function of the inner ear is complex requiring the correct and coordinated expression of many genes. The recent progress in the analyses of the human and other genomes has provided tools for identification of genes involved in hearing. As more and more nucleotide sequence information accumulates, experimental methods of molecular biology are rapidly being supplemented, and partially supplanted, by computational methods. In this study we present comprehensive in silico analyses of a cDNA lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Since the inner ear is composed of dozens of highly specialized cell types, a large amount of important data is lost when this type of approach is adopted, as the unique characteristics of individual cell types do not form part of the analysis. For example, in the study by Klockars et al (2003), oncomodulin and prestin were not identified as inner ear transcripts, yet they are reported to be expressed selectively in outer hair cells (Zheng et al, 2000(Zheng et al, , 2002. A likely explanation for this result is that despite the high expression of the prestin and oncomodulin transcripts in outer hair cells, their overall expression in the mixture of inner ear cells is relatively low.…”
Section: Inner Ear Cdna Librariesmentioning
confidence: 55%
See 4 more Smart Citations
“…Since the inner ear is composed of dozens of highly specialized cell types, a large amount of important data is lost when this type of approach is adopted, as the unique characteristics of individual cell types do not form part of the analysis. For example, in the study by Klockars et al (2003), oncomodulin and prestin were not identified as inner ear transcripts, yet they are reported to be expressed selectively in outer hair cells (Zheng et al, 2000(Zheng et al, , 2002. A likely explanation for this result is that despite the high expression of the prestin and oncomodulin transcripts in outer hair cells, their overall expression in the mixture of inner ear cells is relatively low.…”
Section: Inner Ear Cdna Librariesmentioning
confidence: 55%
“…The Soares NMIE library was derived from the pooled inner ear tissue of 170 mice (http://image.llnl.gov/ image/bin/libinfo; Table 1(4)). Of the 1536 clones in the library, 147 displayed preferential in silico expression in the inner ear and only 13 of these clones represented known genes (Klockars et al, 2003). Interestingly, 91 of the 147 clones appeared to be inner ear specific, representing only approximately 6% of the clones in this library (Klockars et al, 2003).…”
Section: Inner Ear Cdna Librariesmentioning
confidence: 95%
See 3 more Smart Citations